The Role of Work Stress in Mediating the Influence of Emotional Intelligence and Spiritual Intelligence on Nurse Performance at Bunda Hospital Kandangan Surabaya - Niken Revalasha; Muhadjir Anwar; Hesty Prima Rini (Transpublika Publisher, 2024)
The significance of having human resources within the company is one of the most important elements in order for a business or company to run well: The aim of this research is to identify the effects of: (1) Emotional Intelligence, (2) Spiritual Intelligence, (3) Stress related to emotional intelligence, (4) Stress related to spiritual intelligence, to the nurse performance. The samples taken for the research are the entire nurses in